The Individual and the Collective: Sociological Influences on Lacan's Concept of the Relation Subject—Other - Schrans, David (Frontiers in Psychology, 2018)
In this conceptual analysis we discuss the sociological influences on Lacan's conceptualization of the relation between the subject and the other. In his writings predating World War II Lacan defines this relation in terms of identification. However, from 1953 onward he defines it in terms of the subject of speech and the Symbolic Other. It is a popular notion to characterize this change in terms of a radical breach, influenced by the reading of Lévi-Strauss. However, through a close reading of both Lacan's early writings and their Durkheimian influences we will demonstrate that what has changed, is Lacan's conceptualization of the relation between the individual and the collective. This change was gradual rather than sudden. Moreover, it can be situated within the theoretical evolution of the contiguous fields of sociology, anthropology and psychoanalysis. Thus we reject the idea of a breach within his own thought and with what came before him. We will establish our point through a summary of how the relation between the individual and the collective was theorized before Lacan. Durkheim conceptualized this relation as dual: the individual and the collective are radically separated. Mauss attempted to unify the field of anthropology through the holistic concept of the total man. In Lévi-Straus's formalization the individual becomes a function within a structured, Symbolic system. Finally, a reading of Lacan's publications concerning the notion of the logic of the collective will testify to his attempts at formulating a notion of the subject that asserts itself against this collective while at the same time retaining its nature of a logical function. This is the conundrum that Lacan will confront time and again throughout his teachings. Lévi-Strauss merely provided him with the methodological tools of structural anthropology that helped him refine the interrogations that he had already begun.